Analisis Keselamatan dan Kesehatan Kerja pada Stasiun Penggilingan dengan Menggunakan Metode Job Safety Analysis di PT. SGN PG. Rendeng - Akh Sokhibi; Yoga Dwi Arifian; Daffa Althaaf Andika; Andika Wisnujati (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2024)
Occupational Safety and Health is a health and safety condition that guarantees workers and others in the workplace that can impact work productivity. The importance of implementing K3 is an obligation for companies to protect workers from work accidents and work-related diseases. One of the companies that needs to be analyzed K3 is PT. SGN PG. RENDENG Kudus. The purpose of this study was to analyze K3 and provide suggestions for improvements at the grinding station of PT. SGN PG. RENDENG. The method used in analyzing Occupational Safety and Health) is Job Safety Analysis (JSA). The results of this study obtained the condition of the position of the APAR which was not by the placement and the lack of knowledge of workers using PPE so that it could have an impact on workers and the company with the potential for unwanted hazards at the grinding station of PT. SGN PG. RENDENG.